The Implementation of a Doula Grant Program Directed at Families from Economically Vulnerable Backgrounds: A Process Evaluation - Samantha Wall; Kailey Snyder; Becky Baruth; Kara Foster (Health Equity)
Purpose: The purpose of this study was to evaluate the process and overall feasibility of a doula grant program for expectant families from economically vulnerable backgrounds. Design: A mixed-methods process evaluation framework was utilized to examine program feasibility and focused on constructs related to fidelity, dose delivered/dose received, reach, program satisfaction, and limited efficacy testing. Measures: Evaluation constructs were measured using a program tracking document. Program satisfaction and efficacy were examined through a mixed methodology approach utilizing doula surveys and birthing parent interviews. Analysis: Related to survey data, analysis focused on presenting descriptive counts and percentages related to the number of doulas that participated and clients served. Continuous variables were calculated as means and standard deviations and categorical data as counts and percentages. Qualitative data analyses were conducted using a structured deductive thematic approach. Results: The grant program was successfully implemented over an 18-month period, and the program had a high rate of fidelity to the grant processes developed by a Midwestern-based nonprofit organization. The program was satisfactory to doulas and parents, and the largest barrier was communication. A high incidence of prenatal anxiety among the birthing parents was reported. Thematic findings from the birthing parent interviews included the following: the grant application process was effective and easy, birth doulas were greatly valued, and a financial burden was lifted. Conclusion: This grant process can be replicated by other organizations seeking to fill a gap between doula services and the economically vulnerable.